Innovazione e tecnologia all’Istituto Superiore Antincendi - Antonio Del Gallo (GEOmedia, 2019)
The Istituto Superiore Antincendi (ISA) is the physical place where the Italian National Fire Brigade is proposed to its officials and executives, to the companies and public institutions, to the academic and professional world, as a reference point for training in the field of security.